2022
DOI: 10.1155/2022/4586569
|View full text |Cite|
|
Sign up to set email alerts
|

Fibroblasts in Scar Formation: Biology and Clinical Translation

Abstract: Scarring, which develops due to fibroblast activation and excessive extracellular matrix deposition, can cause physical, psychological, and cosmetic problems. Fibroblasts are the main type of connective tissue cells and play important roles in wound healing. However, the underlying mechanisms of fibroblast in reaching scarless wound healing require more exploration. Herein, we systematically reviewed how fibroblasts behave in response to skin injuries, as well as their functions in regeneration and scar format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…HS is a fibroproliferative disease caused by the excessive proliferation of fibroblasts and ECM during wound healing ( Zhang et al, 2020 ). Previous studies have demonstrated that transforming growth factor-β1 (TGF-β1) has a fibrogenic effect in hypertrophic scar fibrosis and plays a crucial part in fibroblast differentiation by regulating the expression of α-smooth muscle actin (α-SMA) in fibroblasts ( Lu et al, 2005 ; Qian et al, 2022 ). α-SMA is a typical marker of the fibroblast contraction phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…HS is a fibroproliferative disease caused by the excessive proliferation of fibroblasts and ECM during wound healing ( Zhang et al, 2020 ). Previous studies have demonstrated that transforming growth factor-β1 (TGF-β1) has a fibrogenic effect in hypertrophic scar fibrosis and plays a crucial part in fibroblast differentiation by regulating the expression of α-smooth muscle actin (α-SMA) in fibroblasts ( Lu et al, 2005 ; Qian et al, 2022 ). α-SMA is a typical marker of the fibroblast contraction phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…This severe fibrosis dysfunction will appear as aesthetic and functional flaws, discomfort, itching, pain, psychological stress, and patient dissatisfaction, reducing range of motion and operational performance while attempting to impose a large cost on people and society. 32 Scar hyperplasia can be avoided and managed based on current knowledge of scar formation biology. 33 There are various effective treatment options for pathological scarring; however, the ideal one remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive fibroblast activation and ECM deposition result in pathological scars from overactive healing processes. This severe fibrosis dysfunction will appear as aesthetic and functional flaws, discomfort, itching, pain, psychological stress, and patient dissatisfaction, reducing range of motion and operational performance while attempting to impose a large cost on people and society 32 . Scar hyperplasia can be avoided and managed based on current knowledge of scar formation biology 33…”
Section: Discussionmentioning
confidence: 99%
“…Although hypertrophic scars and keloids differ in their histopathologic features and clinical appearance, they are both caused by an overproduction of collagen, which continues to be deposited at the site of the wound [2]. The main cells mediating extracellular matrix (ECM) protein turnover are dermal fibroblasts, which are thought to be dysregulated in abnormal scarring disorders, but the exact pathogenesis is still not fully understood [3]. While some scars may be considered as trivial aesthetic skin lesions, abnormal scars can cause a variety of problems ranging from itching, soreness, and pain at the site of injury to systemic effects, such as sleep disturbances, anxiety, depression, and impairment of daily activities.…”
Section: Introductionmentioning
confidence: 99%